Strategies to improve long-term outcomes for patients with chronic kidney disease in China - Jing Liu; Yunying Shi; Yongshu Diao; Xiaoxi Zeng; Ping Fu (Karger Publishers, 2023)
Background: Chronic kidney disease (CKD) is an incurable disease requiring lifelong management. China has a high prevalence of CKD, which disproportionately affects older adults and those with chronic risk factors for CKD development. The rising prevalence of CKD in China places a substantial burden on the general population and the healthcare system. Summary: In China, there are currently many unmet needs for patients with CKD and high-risk individuals, resulting from a lack of education and support to reduce risk factors, delayed diagnoses, limited knowledge of CKD among primary care physicians and poor access to treatments among some patient populations. An integrated, nationwide approach is required to improve the current situation of CKD management in China. There are currently several national healthcare frameworks in place that focus on new major health policies to prevent disease and encourage people to adopt healthier lifestyles, and while they do not directly target CKD, they may have a positive indirect impact. We explore the unmet needs for patients with CKD in China and discuss the potential strategies that may be required to overcome them. Such strategies include improving physician and patient education, establishing a targeted screening programme, supporting patients to improve self-management behaviours, accelerating the creation of medical consortia and medical satellite centres, and migrating from hospital- to community-based management. In additional to policy-driven strategies, development of novel therapies will be key to providing new solutions for the long-term management of CKD.